Discordance between Activated Partial Thromboplastin Time and Anti-factor Xa in Unfractionated Heparin Monitoring: Literature Review - Ciptasari, Debora Purwasista; Pinzon, Rizaldy Taslim; Nugroho, Agung Endro (Majalah Farmaseutik, 2024)
Anticoagulants are prescribed very frequently, but their use is often associated with adverse drug reactions. The optimal monitoring of heparin is unknown, either by aPTT or anti-Xa levels. This paper compares which anti-Xa or aPTT most closely correlates with patients on intravenous heparin. This review also compares the achievement of target goals of unfractionated heparin (UFH) using aPTT and anti-Xa tests. Literature searching was started in June 2024 and ended in July 2024 through some online scientific databases: Scopus, PubMed, Google Scholar, Science Direct, and Willey Online Library. This review includes fifteen studies, at least involving 2,938 patients or 94,038 sets of measurements. The review demonstrates that anti-Xa outperforms aPTT in achieving the therapeutic range of unfractionated heparin, time to therapeutic goal, and dose modification.